If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + 18 = 0 Reorder the terms: 18 + 6c = 0 Solving 18 + 6c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6c = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6c = 0 + -18 6c = 0 + -18 Combine like terms: 0 + -18 = -18 6c = -18 Divide each side by '6'. c = -3 Simplifying c = -3
| 1=21tan(6x+3)-2 | | 7.8+p=12.4 | | (9-x)(4x-1)=0 | | -3x-3+5x-2=-(2x+3) | | 3.88-1.02x=1.38+1.48x | | 4x=9y-2 | | 1.4x+2.1=0.5x+5.7 | | 2+4u=22 | | x^2-16X=-16 | | 2(2n+5)=9(4n+7)+9 | | A+3-20=1 | | (x^4)(3xy^2)= | | 23x=6x-2 | | (4x+3)(2x+7)=274 | | 5-3h=1+h | | 32y=6z | | 2x+6x+5+29= | | -9x^2=-34 | | 6x+2=1x | | 83-y=178 | | 17+g=6-g | | cos^2(c)+2cos(c)+1=0 | | 2x+6x+5+29y=8 | | .1x+56=90 | | 48=4y+8 | | 7e+4=18-3e | | 14x-2x-3=3x-12-18 | | 5(3n+3)=7(8n+3)+6 | | 13Z=23 | | 8b+5n+8= | | 7x+8x-4x-5=61 | | 30=x+10 |